Experienced physicians benefit from analyzing initial diagnostic hypotheses - Adam Bass; Colin Geddes; Bruce Wright; Sylvain Coderre; Remy Rikers; Kevin McLaughlin (Canadian Medical Education Journal, 2013)
Background: Most incorrect diagnoses involve at least one cognitive error, of which premature closure is the most prevalent. While metacognitive strategies can mitigate premature closure in inexperienced learners, these are rarely studied in experienced physicians. Our objective here was to evaluate the effect of analytic information processing on diagnostic performance of nephrologists and nephrology residents.